2016
DOI: 10.1128/jvi.01002-16
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Determinants of Antibody Recognition and Antigenic Drift in the H3 Hemagglutinin of Swine Influenza A Virus

Abstract: Influenza A virus (IAV) of the H3 subtype is an important respiratory pathogen that affects both humans and swine. Vaccination to induce neutralizing antibodies against the surface glycoprotein hemagglutinin (HA) is the primary method used to control disease. However, due to antigenic drift, vaccine strains must be periodically updated. Six of the 7 positions previously identified in human seasonal H3 (positions 145, 155, 156, 158, 159, 189, and 193) were also indicated in swine H3 antigenic evolution. To expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 54 publications
2
74
1
Order By: Relevance
“…The amino acid residues identified in the present study as critical for the antigenic difference between A(H3N2)v and seasonal H3N2 viruses are all located near the RBS in HA, which is in agreement with the observations in other studies that examined H3N2 antigenic evolution (19,23,24). Our study indicated that the amino acid mutations which switched the antigenic phenotype of MN/10 and BJ/92 influenced receptor binding.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The amino acid residues identified in the present study as critical for the antigenic difference between A(H3N2)v and seasonal H3N2 viruses are all located near the RBS in HA, which is in agreement with the observations in other studies that examined H3N2 antigenic evolution (19,23,24). Our study indicated that the amino acid mutations which switched the antigenic phenotype of MN/10 and BJ/92 influenced receptor binding.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we demonstrated that the amino acid substitutions that confer the antigenic phenotype impact both receptor specificity and antibody binding. Our findings provide additional evidence that residues near the HA RBS, especially those in antigenic site B, play significant role in the antigenic evolution of H3N2 viruses (23,24). Seasonal H3N2 viruses experience antigenic drift, which necessitates frequent updates of H3N2 candidate viruses for seasonal influenza vaccines (24,29).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The diversity of contemporary strains co-circulating in the United States has been relatively well characterized in large part due to the US Department of Agriculture (USDA) surveillance efforts operated through the National Animal Health Laboratory Network and the National Veterinary Services Laboratories. The increased reporting and accessibility to publically available sequence data resulted in a more comprehensive genetic and antigenic understanding of circulating strains (Abente et al, 2016; Anderson et al, 2015; Anderson et al, 2013; Lewis et al, 2014). Furthermore, it facilitated the early detection of novel HA introductions into the swine population, such as a 2010–11 human H3 that has sustained onward transmission in the pig population (Rajao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%